Assessment of asbestos exposure in Kyrgyzstan through analysis of raw and processed materials, air samples and human lung tissue - Zhyldyz Kurzhunbaeva; Ruggero Vigliaturo; Giulia Pia Servetto; Barbara Bertoglio; Giovanni Cecchetto; Nurzhan Tulepbergenov; Ekaterina Mindiyarova; Rano Kasymova; Kenesh Dzhusupov; Silvana Capella; Elena Belluso; Claudio Colosio; et al. (Scientific Reports)
Abstract Asbestos still represents a major public health problem on a global scale. In Central Asia chrysotile is still mined and used, claiming that it is safer with respect to amphibole asbestos within certain concentrations. However, the problem of asbestos exposure in Central Asia and its consequences on human health have been poorly investigated. We analysed, for the first time, samples of raw and wrought material coming from one of the two asbestos-cement industries, currently active, located near the city of Bishkek, the capital of Kyrgyzstan, as well as air samples collected on different sites of Bishkek and Kant and lung tissues taken from the general population during clinical autopsies. Air samples have been analyzed using a scanning electron microscopy (SEM) equipped with energy dispersive spectroscopy (EDS). Heavy air asbestos pollution was detected in Kant (30.2 ff/L), while Bishkek had lower levels. Lung tissue analysis in the general population, carried out using both SEM and transmission electron microscopy (TEM) with EDS, revealed the presence of both chrysotile and amphibole asbestos. Such findings underline that, even in countries where the use of asbestos is allowed based on the presumed pureness of chrysotile used and the lower carcinogenic potential of chrysotile compared to amphibole asbestos, the general population could be exposed also to amphibole asbestos.